Expresión de Her2/neu en carcinoma gástrico en el área metropolitana de Bucaramanga en el periodo 2006 a 2009 (2013)
Introduction: gastric cancer has become a public health problem in the world and in Colombia is one of the leading causes of mortality. The oncoprotein Her/2 neu has shown to be an independent bad prognostic factor with a variable expression ranging from 8 - 91% and has been associated with an aggressive disease and a lesser response to treatment. Aim: to determinate the frequency of Her/2 neu and its expression in gastric carcinoma, also its histopathologic correlation in patients from the Bucaramanga Metropolitan Area during 2006 to 2009. Materials and methods: we conducted an observational cross-sectional study with a population of 409 cases from the Population based Cancer Registry from Bucaramanga Metropolitan Area. The information was collected from clinical history and parafn blocks. The immunochemistry was made with manual HERCEPTEST method. Scores 0 and 1 were interpretated as negative, score 2 as equivocal and score 3 as positive. The samples that were equivocal underwent fuorescence immunohistochemistry in situ. Results: males predominated with 243 cases, the intestinal type was the more prevalent with 230 cases, Her/2 neu expression was positive in 46 cases and there was no signifcant statistical association with histopathological subtype or gender. Conclusions: expression of Her/2 neu was positive in 11.2% of gastric carcinomas of patients from Bucaramanga Metropolitan Area, this fnding is consistent with other reports, and neither there was any statistical signifcance association with subtype and gender. (MÉD.UIS.2013;26(2):21-8).